Fish Species Composition in Hau River Basin at Hau Giang Province - Ngoc, Le Kim; Huyen, Son Ngoc; Hue, Nguyen Thi Ngoc; Anh, Le Hoang; Dep, Tran Van; Dong, Nguyen Thanh; Dinh, Tran Dac; Hung, Ha Phuoc; Hoang, To Thi My; Vang, Nguyen Thi; Toan, Vo Thanh; Tinh, Nguyen Trung; et al. (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 1DO - 10.25073/2588-1140/vnunst.4723, 2018)
This study was conducted from December 2015 to November 2016 at 44 sampling sites in the Hau River Basin at Hau Giang Province. The analysis results recorded 125 fish species belonging to 19 Orders and 46 families. The fish species composition was more diverse in wet season (119 species) than that in dry season (101 species). Of 19 orders, Cypriniformes, Siluriformes, Anabatiformes, Perciformes and Gobiformes had the highest number of species recorded during wet and dry seasons. The fish species composition had higher diversity in the ecological region regulated by east sea tide than the ecological region regulated by west sea tide and the contiguous ecological region. Keyword Rish species composition, Hau Giang, Hau river References [1] Vũ Vi An, Đoàn Văn Tiến, Lâm Phước Khiêm & Nguyễn Nguyễn Du, Đánh giá sản lượng khai thác của ngư dân vùng Đồng bằng sông Cửu Long, Tuyển tập Nghề cá sông Cửu Long, 428-436, 2011. [2] Mai Đình Yên, Nguyễn Văn Trọng, Nguyễn Văn Thiện, Lê Hoàng Yến & Hứa Bạch Loan, Định loại cá nước ngọt Nam bộ, Nxb Khoa học và Kỹ thuật, Hà Nội, 1992. [3] Trương Thủ Khoa & Trần Thị Thu Hương, Định loại cá nước ngọt vùng Đồng bằng sông Cửu Long, Tủ sách Đại học Cần Thơ, Cần Thơ, 1993. [4] Đoàn Văn Tiến & Mai Thị Trúc Chi, Quan Trắc sản lượng cá đánh bắt ở Đồng bằng sông Cửu Long, Hội thảo quốc gia về phát triển thủy sản vùng hạ lưu sông Mekong, Việt nam, Nxb Nông nghiệp, 2005. [5] Trần Đắc Định, Koichi, S., Nguyễn Thanh Phương, Hà Phước Hùng, Trần Xuân Lợi, Mai Văn Hiếu & Kenzo, U., Mô tả định loại cá Đồng bằng sông Cửu Long, Việt Nam, Nxb Đại học Cần Thơ, Cần Thơ, 2013. [6] Viện Quy hoạch thủy lợi miền Nam, Quy hoạch xây dựng thủy lợi tỉnh Hậu Giang đến năm 2020 và tầm nhìn đến năm 2030 (Tập 1 Báo cáo tổng hợp), Thành phố Hồ Chí Minh, 2012. [7] Phạm Nhật, Vũ Văn Dũng, Đỗ Quang Huy, Nguyễn Cử, Lê Nguyên Ngật, Nguyễn Hữu Dực, Nguyễn Thế Nhã, Võ Sĩ Tuấn, Phan Nguyên Hồng, Nguyễn Văn Tiến, Đào Tấn Hổ, Nguyễn Xuân Hòa, Nick Cox & Nguyễn Tiến Hiệp, Sổ tay hướng dẫn điều tra và giám sát đa dạng sinh học, Nxb Giao thông vận tải, Hà Nội, 2003. [8] Pravdin, I. F., Hướng dẫn nghiên cứu cá (Phạm Thị Minh Giang dịch), Nxb Khoa học và Kỹ thuật, Hà Nội, 1973. [9] Nguyễn Văn Hảo & Ngô Sỹ Vân, Cá nước ngọt Việt Nam, Nxb Nông Nghiệp, Hà Nội, 2001. [10] Nguyễn Văn Hảo, Cá nước ngọt Việt Nam, Nxb Nông nghiệp, Hà Nội, 2005. [11] Nguyễn Văn Hảo, Cá nước ngọt Việt Nam, Nxb Nông nghiệp, Hà Nội, 2005. [12] Rainboth, W. J., Fishes of the Cambodian Mekong, FAO, Roma, 1996. [13] Froese, R. & Pauly, D., FishBase, World Wide Web electronic publication, 2017, truy cập ngày 10/06/2017. www.fishbase.org [14] Nguyễn Ngọc Anh, 2016. Hạn - mặn lịch sử 2016 ở Đồng bằng sông Cửu Long: bài học kinh nghiệm và những giải pháp ứng phó, Tạp chí Khoa học và Công nghệ Việt Nam, Hà Nội, 19/01/2018, http://www.khoahocvacongnghevietnam.com.vn/khcn-trung-uong/13123-han-man-lich-su-2016-0-dong-bang-song-cuu-long-bai-hoc-kinh-nghiem-va-giai-phap-ung-pho.